The use of segmental bone resection to assist in a tension-free cleft palate repair - GÜNEREN, Ethem; GÜNEREN, ETHEM (My University, 2022)
The traditional two-flap palatoplasty technique described by Veau-Wardill-Kilner is a two-flap palatoplasty suggests a posterior pushback movement of flaps should require an intact pedicle. Even a proper dissection of greater palatine vessels is done, some sort of tension burdens on the flaps due to the traction of the pedicle is inevitable. In addition to that, the right-angled flexion of the pedicle at the posteromedial bony corner of foramina palatinum majus diminishes blood flow. Particularly, in wide clefts, tight approximation of flap compromises the wound healing and resulting fistulas. A segmental bone resection from posteromedial wall of foramen palatinum majus as an outfracturing fashion is performed to assist a tension-free cleft palate repair. The more release of the pedicle from its hole loosens the flaps. It provides an easy posteromedial transposition of tissues. This maintains also most push-back movement of flaps.